Intelligent H2S release coating for regulating vascular remodeling - Bingyang Lu; Xiao Han; Ansha Zhao; Dan Luo; Manfred F. Maitz; Haohao Wang; Ping Yang; Nan Huang (Bioactive Materials, 2021)
Coronary atherosclerotic lesions exhibit a low-pH chronic inflammatory response. Due to insufficient drug release control, drug-eluting stent intervention can lead to delayed endothelialization, advanced thrombosis, and unprecise treatment. In this study, hyaluronic acid and chitosan were used to prepare pH-responsive self-assembling films. The hydrogen sulfide (H2S) releasing aspirin derivative ACS14 was used as drug in the film. The film regulates the release of the drug adjusted to the microenvironment of the lesion, and the drug balances the vascular function by releasing the regulating gas H2S, which comparably to NO promotes the self-healing capacity of blood vessels. Drug releasing profiles of the films at different pH, and other biological effects on blood vessels were evaluated through blood compatibility, cellular, and implantation experiments. This novel method of self-assembled films which H2S in an amount, which is adjusted to the condition of the lesion provides a new concept for the treatment of cardiovascular diseases.